Heatwave risks and impacts : Exploring community perceptions and adaptive strategies in Fetakgomo Tubatse local municipality - Maepa, Mahlabane Linah (Stellenbosch : Stellenbosch University, 2026)
Thesis (MPhil)--Stellenbosch University, 2026.